2011
DOI: 10.1111/j.1600-0412.2011.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of gynecological cancer surveillance in women belonging to hereditary nonpolyposis colorectal cancer (Lynch syndrome) families

Abstract: Currently available published studies on gynecological cancer surveillance in women with HNPCC do not adequately allow for evidence-based clinical decisions. Detection of endometrial cancer or hyperplasia in nonsymptomatic women belonging to an HNPCC family is improved by adding routine endometrial sampling along with transvaginal ultrasound for surveillance visits. No benefit was shown for ovarian cancer surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 26 publications
0
70
0
5
Order By: Relevance
“…Recommended surveillance includes: colonoscopy every 1-2 years starting at age 25 (or 5 years younger than the youngest affected family member if <30 years), 2 yearly upper endoscopy starting age 30 in families with gastric cancer or at high ethnic risk. While some guidelines recommend annual per vaginal speculum examination, pelvic ultrasound, CA-125 analysis, and urinalysis, there is currently no high-level evidence for benefit (Auranen and Joutsiniemi, 2011;Vasen et al, 2013). Surveillance for other Lynch-associated cancers is not recommended outside of clinical trials, due to low sensitivity and specificity of currently available investigations (Rubenstein et al, 2015;Stoffel and Kastrinos, 2014;Vasen et al, 2013).…”
Section: Rev Ised Bethesda Guidelinesmentioning
confidence: 99%
“…Recommended surveillance includes: colonoscopy every 1-2 years starting at age 25 (or 5 years younger than the youngest affected family member if <30 years), 2 yearly upper endoscopy starting age 30 in families with gastric cancer or at high ethnic risk. While some guidelines recommend annual per vaginal speculum examination, pelvic ultrasound, CA-125 analysis, and urinalysis, there is currently no high-level evidence for benefit (Auranen and Joutsiniemi, 2011;Vasen et al, 2013). Surveillance for other Lynch-associated cancers is not recommended outside of clinical trials, due to low sensitivity and specificity of currently available investigations (Rubenstein et al, 2015;Stoffel and Kastrinos, 2014;Vasen et al, 2013).…”
Section: Rev Ised Bethesda Guidelinesmentioning
confidence: 99%
“…Annual endometrial sampling may be considered, but the benefit is uncertain. 55,[58][59][60][61][62] Routine transvaginal ultrasound and serum CA-125 testing are not endorsed because they have not been shown to be sufficiently sensitive or specific, 55,[59][60][61][62][63] but the panel recognized that there may be circumstances in which the clinician may find these tests helpful. An observational study showed that hormonal contraceptive use is associated with lower risk of endometrial cancer in carriers of MMR mutations (hazard ratio [HR], 0.39; 95% CI, 0.23-0.64, P<.001).…”
Section: Surveillance For Patients With Lynch Syndromementioning
confidence: 99%
“…We identified three primary studies 107,190,191 and four reviews 65,167,192,193 which were critically appraised in relation to the UK context and the decision problem.…”
Section: Literature Review Of the Effectiveness Of Surveillance For Ementioning
confidence: 99%
“…Auranen and Joutsiniemi (2011) 192 conducted a systematic review of gynaecological cancer screening in women belonging to LS families, which had five included studies. 190,191,[194][195][196] In our review, the study by Lécuru and colleagues (2008) 195 was excluded because the abstract suggested that there was no comparator for the surveillance strategy.…”
Section: Existing Reviewsmentioning
confidence: 99%